Enhancing bio-oil quality and energy recovery by atmospheric hydrodeoxygenation of wheat straw pyrolysis vapors using Pt and Mo-based catalysts. Issue 4 (17th February 2020) - Eschenbacher, Andreas; Saraeian, Alireza; Shanks, Brent H.; Jensen, Peter Arendt; Li, Chengxin; Duus, Jens Øllgaard; Hansen, Asger Baltzer; Mentzel, Uffe Vie; Henriksen, Ulrik Birk; Ahrenfeldt, Jesper; Jensen, Anker Degn
Abstract : Atmospheric hydrodeoxygenation (HDO) of wheat straw fast pyrolysis vapors was studied as a promising route for the production of renewable liquid transportation fuels. Abstract : Atmospheric hydrodeoxygenation (HDO) of wheat straw fast pyrolysis vapors was studied as a promising route for the production of renewable liquid transportation fuels. The performance of TiO2 -supported Pt (0.5 wt%) and MoO3 (10 wt%) catalysts was compared to an industrial Mo-based catalyst using a bench scale reactor operated at atmospheric pressure and up to high biomass-to-catalyst ratios (B:C). Mass and energy balances were complemented by detailed bio-oil characterization including advanced methods such as GC×GC-ToF/MS or -FID and 13 C NMR. At 50 vol% H2, all three HDO catalysts effectively reduced the oxygen content of the bio-oils to ∼7–12 wt% (dry basis) compared to a non-catalytic reference (23 wt% O). MoO3 /TiO2 was least efficient in conversion of acids (TAN = 28 mg per KOH), while Pt/TiO2 and MoO3 /Al2 O3 obtained oils with TAN ∼ 13 mg KOH/g (non-catalytic = 66 mg KOH/g). Compared to the TiO2 -supported catalysts, the industrial Mo/Al2 O3 catalyst produced higher yields of coke at the expense of condensed bio-oil. MoO3 /TiO2 performed similar to Pt/TiO2 in terms of deoxygenation and energy recovery of condensed bio-oil, and by increasing the H2 concentration to 90 vol% the energy recovery of bio-oil increased to 39 and 42% at 8 and 10 wt% O (d.b.), respectively. Pt/TiO2 showed the highest selectivity to aliphatics and the lowest coke yields, e.g. the coke yield at B:C ∼ 8 was only 0.6 wt% of fed biomass. This study demonstrates that by using low-pressures of hydrogen and appropriate HDO catalysts, the quality of bio-oil can be improved without severely compromising its quantity (carbon yield) as observed under catalytic fast pyrolysis conditions.